2016
DOI: 10.1016/j.jnucmat.2015.08.035
|View full text |Cite
|
Sign up to set email alerts
|

Cavitation damage prediction for the JSNS mercury target vessel

Abstract: The liquid mercury target system for the Japan Spallation Neutron Source (JSNS) at the Materials and Life science experimental Facility (MLF) in the Japan Proton Accelerator Research Complex (J-PARC) is designed to produce pulsed neutrons. The mercury target vessel in this system, which is made of type 316L stainless steel, is damaged by pressure wave-induced cavitation due to proton beam bombardment. Currently, cavitation damage is considered to be the dominant factor influencing the service life of the targe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 27 publications
1
12
0
Order By: Relevance
“…The left-hand-side figure shows relation between the displacement velocity of the target vessel at the time of proton beam injection and the beam power P (kW) and the peak current density Q (J/cc). For the beam power less than 500 kW, we had observed that the displacement velocity became higher as the peak current density in the proton beam profile increased at the same beam power, concluding that it could be fitted with a linear approximation (dotted line) as a function of the product of P  and Q  with appropriate parameters of  and  where =0.4375 and =0.5625 [12]. The present data taken in the higher beam power than 500 kW are also described with the linear relation.…”
Section: Operational History Of Spallation Neutron Source At J-parcmentioning
confidence: 88%
“…The left-hand-side figure shows relation between the displacement velocity of the target vessel at the time of proton beam injection and the beam power P (kW) and the peak current density Q (J/cc). For the beam power less than 500 kW, we had observed that the displacement velocity became higher as the peak current density in the proton beam profile increased at the same beam power, concluding that it could be fitted with a linear approximation (dotted line) as a function of the product of P  and Q  with appropriate parameters of  and  where =0.4375 and =0.5625 [12]. The present data taken in the higher beam power than 500 kW are also described with the linear relation.…”
Section: Operational History Of Spallation Neutron Source At J-parcmentioning
confidence: 88%
“…For example it was revealed 2 , 3 that sonoluminescence can be induced in liquid metals by creating cavitation through acoustic excitation. The dynamics of cavitation bubbles particularly in mercury has received attention after large scale cavitation erosion of structural elements were observed in spallation neutron sources 4 , 5 . While cavitation plays an important role in various technological processes of modern metallurgy 6 8 it also allows to probe for tensile strength thresholds 9 12 .…”
Section: Introductionmentioning
confidence: 99%
“…The maximum depth of a pit was approximately 25 µm [27]. This depth is slightly deeper than the predicted damage depth of approximately 10 -15 µm, based on a prediction method proposed in a previous study [28].…”
Section: Cavitation-damage-mitigation With Narrow Channel Flowmentioning
confidence: 53%